Case report: Laryngospasm following ethanol ablation of a parathyroid nodule in a dog with primary hyperparathyroidism - Rank, Kaitlyn; Lynch, Alex M.; Green, Randolph; Reed-Jones, Leslie; Harrell, Karyn; Ueda, Yu (Frontiers in Veterinary Science, 2023)
A 12-year-old female spayed dachshund was presented for emergency assessment of respiratory distress, characterized by inspiratory dyspnea with stridor. Percutaneous ultrasound-guided ethanol ablation of a functional parathyroid tumor was performed 72-hours earlier for management of primary hyperparathyroidism. The dog was hypocalcemic (ionized calcium 0.7 mmol/L, reference interval: 0.9-1.3 mmol/L) at the time of presentation and had evidence of laryngospasm on a sedated oral exam. The dog was managed conservatively with supplemental oxygen, anxiolysis, and parenteral calcium administration. These interventions were associated with rapid and sustained improvement in clinical signs. The dog did not demonstrate any recurrence of signs afterwards. To the authors’ knowledge, this is the first description of laryngospasm following ethanol ablation of a parathyroid nodule in a dog that developed hypocalcemia.